Selection of high nitrogen fixation chickpea genotypes under drought stress conditions using multi-environment analysis - Istanbuli, Tawffiq; Alsamman, Alsamman M.; Al-Shamaa, Khaled; Abu Assar, Ahmed; Adlan, Muhammed; Kumar, Tapan; Tawkaz, Sawsan; Hamwieh, Aladdin (Frontiers in Plant Science, 2025)
IntroductionChickpea (*Cicer arietinum* L.) is an important pulse crop mainly grown in marginal lands around the world. Drought stress highly impacts symbiotic nitrogen fixation (SNF) in chickpeas, which can limit productivity. Therefore, selecting high nitrogen fixation chickpea genotypes that can tolerate water stress is important for breeding programs.MethodsA total of 204 chickpea genotypes were assessed in eight different environments across Lebanon during the 2016 and 2017 growing seasons, under both rainfed and irrigated conditions. The study employed an Alpha Lattice design with two replications at two distinct locations. Data were collected for yield and nodule characteristics, then subjected to AMMI and GGE biplot analysis.Results and DiscussionThe AMMI analysis indicated that genotype (G), environments (E), and genotype × environment interaction (GEI) had significant effects on grain yield (P<0.001), highlighting the presence of genetic variation and the potential for selecting stable genotypes. The findings revealed that the environmental effect predominantly influenced chickpea grain yield, with GEI following, and G having the least impact. Environment explained 34.5% of the total (G + E + GE) variation, whereas G and GEI captured 16.4% and 24.3%, respectively. According to grain yield (GY), genotype IG70399 demonstrated the highest performance across all environments, while genotype IG8256 displayed the most consistent performance across different conditions. In a rainfed environment, genotype IG73394 had higher nodulation, while IG70384 and IG70410 had higher nodulation biomass (NB) under an irrigated environment. The NB for ten highly tolerant genotypes increased by 24% compared to the two susceptible genotypes under drought stress conditions, while the NB for these ten genotypes increased by 14.6% compared to all studied genotypes.